High Wind Speed Performance of AeroMINE at Pilot-Scale. Issue 4 (1st May 2022) - Houchens, B C; Marian, D V; Pol, S; Westergaard, C H
Abstract: AeroMINEs consist of a mirrored pair of foils that have no external moving parts. A low-pressure region is created between the foils. The foils are hollow and the low-pressure side skins contain orifices (air-jets) that allow air to flow from the interior of the foil to the exterior flow, driven by the suction between the mirrored pair. This flow is ducted to an internal turbine and generator, producing electricity. A series of pilot-scale field (1-m chord) demonstrations were performed on AeroMINEs. These included both low wind speed tests (<5 m/s) and high wind speed tests (>9 m/s) at the Sandia National Laboratories Scaled Wind Farm Technology site in Lubbock, Texas, USA. Here the performance in high wind speed conditions is studied while varying the air-jet area. An efficiency of 25%, or 42% of Betz limit, was achieved for the maximum air-jet area.